2000
DOI: 10.1002/(sici)1097-4636(20000615)50:4<518::aid-jbm7>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Formation of calcium phosphate/collagen composites through mineralization of collagen matrix

Abstract: Several types of calcium phosphate/collagen composites, including noncrystalline calcium phosphate/collagen, poorly crystalline carbonate-apatite (PCCA)/collagen, and PCCA + tetracalcium phosphate/collagen composites, were prepared through the mineralization of collagen matrix. The type I collagen was presoaked with a PO(3-)(4) containing solution and then immersed in a Ca(2+) containing solution to allow mineral deposition. The solution of 0.56 M sodium dibasic phosphate (Na(2)HPO(4)) with a pH of nearly 14 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(185 citation statements)
references
References 69 publications
3
171
0
Order By: Relevance
“…However, porosities of only 60-70% (Vance et al 2005) and 80-85% (Kim et al 2005) are reported. With a similar CP process and commercially available Gelfix scaffolds, Yaylaoglu et al, Kose et al and Du et al claim similar material results to our study of precipitated CP to a collagen scaffold (Du et al 2000, Kose et al 2004, Yaylaoglu et al 1999. However no data on the mechanical properties of these scaffolds is available to support their assumption.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, porosities of only 60-70% (Vance et al 2005) and 80-85% (Kim et al 2005) are reported. With a similar CP process and commercially available Gelfix scaffolds, Yaylaoglu et al, Kose et al and Du et al claim similar material results to our study of precipitated CP to a collagen scaffold (Du et al 2000, Kose et al 2004, Yaylaoglu et al 1999. However no data on the mechanical properties of these scaffolds is available to support their assumption.…”
Section: Discussionsupporting
confidence: 82%
“…However, as each scaffold consists of some phase which is not found naturally in the human body, they have all exhibited drawbacks with biocompatibility, biodegradability or osteconductivity (Rezwan et al 2006). Natural collagen scaffolds coated with HA or CP have been investigated using a bi-phasic immersion process with promising results in terms of their biological performance (Du et al 2000, Yaylaoglu et al 1999. However, this study used commercially available collagen sheets with initial porosities of 50-60% which is very low compared to collagen sheets developed by O'Brien et al (2004) with a porosity of 99.5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen molecules and the nanocrystals of biological apatite assembled into mineralized fibrils are approximately 6-nm-diameter and 300-nm-long [31,35,38,510,589]. Although the complete mechanisms involved in the bone building strategy are still unclear, the strengthening effect of apatite nanocrystals in calcified tissues might be explained by the fact that the collagen matrix is a load transfer medium and thus transfers the load to the intrinsically rigid inorganic nanocrystals.…”
Section: Biocomposites With Collagenmentioning
confidence: 99%
“…Incorporating HAP, an important inorganic component of bone ECM, into synthetic microspheres to fabricate a composite material with enhanced osteoconductivity is one example of a composite microsphere. The nanoscale organization of HAP within a polymeric matrix provides increased hydrophilicity, future science group Review Zhang, Eyster & Ma wettability, surface area and surface roughness, which leads to enhanced osteoblast adhesion and osteoconductivity and better bonding to host bone for long-term functionality [126,127]. One approach for organizing HAP at the nanoscale is through in situ precipitation of apatite crystals within a polymer or macromolecular solution [122,123].…”
Section: Injectable Microspheres For Tissue Engineeringmentioning
confidence: 99%